Ways of Narrating Memory: Hannah Arendt’s "Eichmann in Jerusalem" and Steven Spielberg’s "Schindler’s List" / Formas de narração da memória: “Eichmann em Israel”, de Hannah Arendt e “A Lista de Schindler”, de Steven Spielberg - Heuer, Wolfgang (Revista Direito e Práxis, 2012)
DOI 10.12957/dep.2012.3545 Abstract It is self-evident that events of the past are bound to places and acting people, they are playing a decisive role for memory and history. Meaning and importance of places and actions in the past depend on their contexts and each change inevitably also changes the meaning of the events itself. I would like to demonstrate some of the consequences of such a change by comparing Hannah Arendt’s “Eichmann in Jerusalem“ with Steven Spielberg’s “Schindler’s List“ who decontextualized a factual story and thus changed places and acting people. But before doing this, I would like to emphasize the importance which places and acting people play for memory and history with some perhaps unusual remarks. They refer to the official European history and politics which seem to be marked by the absence of places and acting people. Keywords: Eichmann in Jerusalem, Hannah Arendt, Schindler’s List, Steven Spielberg Resumo É autoevidente que acontecimentos do passado estão condicionados a lugares e a pessoas atuantes, que têm papel fundamental na memória e na história. O significado e a importância de lugares e de ações do passado dependem de seu contexto e cada mudança sua inevitavelmente altera também os próprios acontecimentos. Eu gostaria de demonstrar algumas das consequências de tal mudança comparando “Eichmann em Israel”, de Hannah Arendt com “A Lista de Schindler”, de Steven Spielberg, que descontextualizou uma história real e, assim, modificou lugares e pessoas de atuação. Mas antes disso, eu gostaria de enfatizar a importância que lugares e pessoas atuantes têm a memória e na história com alguns comentários talvez inusitados. Eles fazem referência à História oficial e à política da Europa que parecem ser marcados pela ausência de lugares e de pessoas de atuação marcante. Palavras-chaves: Eichmann em Israel, Hannah Arendt, Lista de Schindler, Steven Spielberg